Staphylococcus aureus bacteremias following liver transplantation: a clinical analysis of 20 cases - Zhou JD; Huang H; Liu S; Yu P; Wan QQ (Dove Medical Press, 2015)
Jiandang Zhou,1,2 Hui Huang,3 Shan Liu,4 Ping Yu,2 Qiquan Wan5 1Department of Clinical Laboratory, the Third Xiangya Hospital of Central South University, 2Department of Immunology, Xiangya School of Medicine, Central South University, 3Nursing Department, the Third Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of China; 4Adelphi University College of Nursing and Public Health, New York, NY, USA; 5Department of Transplant Surgery, the Third Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of China Background: To describe the incidence, clinical characteristics, and outcomes of Staphylococcus aureus bacteremia after liver transplantation and investigate the drug resistance of S. aureus to frequently used antibiotics to provide evidence for clinical prevention and therapy.Materials and methods: In a double-center retrospective study, blood cultures positive for S. aureus were obtained from January 1, 2001 to December 31, 2014. The BACTEC 9120 blood culture system and the Vitek-2 system were used to process blood samples and identify species, respectively. We also collected these patients’ data to confirm clinical and laboratory characteristics.Results: Twenty of 275 (7.3%) liver recipients developed S. aureus bacteremia during the study period. The median time to the onset of S. aureus bacteremias was 6 days after liver transplantation and all episodes of bacteremias were early onset. The lung was the most common source of primary infection, followed by the intra-abdominal/biliary tract. A total of nine (45%) liver recipients died due to S. aureus bacteremias. Of these 20 S. aureus cases, 80% were methicillin-resistant. S. aureus was highly resistant to erythromycin and penicillin (resistance rate >90%). No S. aureus resistant to glycopeptides and oxazolidone antibiotics was observed. There were seven (35%) liver recipients with an inappropriate antibiotic therapy. Between the periods of 2001–2007 and 2008–2014, the distribution of methicillin-resistant S. aureus was not significantly different (P=1.000). Pneumonia as a predominant primary source, a high body temperature, abnormal blood pressure, and decreased platelets, which occurred in the early period after liver transplantation, as well as high morbidity and mortality, were the main characteristics of S. aureus bacteremias.Conclusion: S. aureus led to severe bacteremias in liver recipients, with high morbidity and mortality, and the majority of them comprised methicillin-resistant S. aureus. Keywords: liver transplantation, Staphylococcus aureus, bacteremia, drug resistance